2023
DOI: 10.1039/d3ra02011h
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the performance of Auy/Nix/TiO2NTs photoanodes for photoelectrochemical water splitting

Shaimaa K. Mohamed,
Amany M. A. Bashat,
Hassan M. A. Hassan
et al.

Abstract: Water splitting using photoelectrochemical (PEC) techniques is thought to be a potential method for creating green hydrogen as a sustainable energy source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…41 Actually, the LSPR effect is predicated upon synchronized unconfined charge carrier oscillation on gold surfaces 42 and manifests resonance with photons present in the visible-light spectrum. 43 The interaction between gold surface and photons results in generation of hot electrons/holes. 44 Subsequently, the hot electron (e − ) transfer to the conduction band (CB) of semiconductors thereby results in the origination of hot holes on the surface of Au nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Actually, the LSPR effect is predicated upon synchronized unconfined charge carrier oscillation on gold surfaces 42 and manifests resonance with photons present in the visible-light spectrum. 43 The interaction between gold surface and photons results in generation of hot electrons/holes. 44 Subsequently, the hot electron (e − ) transfer to the conduction band (CB) of semiconductors thereby results in the origination of hot holes on the surface of Au nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been reported that utilization of localized surface plasmon resonance (LSPR) induced by Au nanoparticles is a highly effective approach in enhancing the performance of numerous semiconductors . Actually, the LSPR effect is predicated upon synchronized unconfined charge carrier oscillation on gold surfaces and manifests resonance with photons present in the visible-light spectrum . The interaction between gold surface and photons results in generation of hot electrons/holes .…”
Section: Introductionmentioning
confidence: 99%